Neonatal Impedance Cardiography in Asphyxiated Piglets—A Feasibility Study - Berisha, Gazmend; Solberg, Rønnaug; Klingenberg, Claus; Solevåg, Anne Lee (Frontiers in Pediatrics, 2022)
Objectives Impedance cardiography (ICG) is a non-invasive method for continuous cardiac output measurement and has the potential to improve monitoring and treatment of sick neonates. PhysioFlow® is a signal-morphology ICG-system showing promising results in adults with low and high cardiac output, but no data from neonates or neonatal models exist. The aim of this study was to investigate PhysioFlow® feasibility in asphyxiated newborn piglets. Methods Fifteen piglets, under continuous arterial heart rate (HR) and blood pressure (BP) monitoring, were asphyxiated until asystole. Cardiopulmonary resuscitation was performed and the piglets monitored after return of spontaneous circulation (ROSC). Arterial lactate was measured at baseline, every 5 min throughout asphyxiation, at asystole, and at 10 min and later every 30 min after ROSC. PhysioFlow® measured cardiac stroke volume (SV) and HR, and calculated cardiac index (CI) (L/m2/min). Registrations with a signal quality < 75% were excluded, and registrations recorded for 30 min from start of asphyxia analyzed. Pearson correlations were calculated for CI; and HR, mean BP and blood lactate. Results The piglets were asphyxiated for median (interquartile range) 30 (20–35) min and had a lactate at asystole of 15.0 (9.1–17.0) mmol/L. Out of a total of 20.991 registrations in all animals combined, there were 10.148 (48.3%) registrations with a signal quality ≥ 75%. Signal quality ≥ 75% varied in individual piglets from 7 to 82% of registrations. We analyzed 1.254 registrations recorded 30 min from initiation of asphyxia, i.e., in piglets with brief asphyxia times, this included cardiopulmonary resuscitation and post-ROSC observation. There was a positive correlation between CI and SVI (r = 0.90, p < 0.001), and between CI and HR (r = 0.446, p < 0.001). There was no correlation between CI, or mean BP or lactate (p = 0.98 and 0.51, respectively). Conclusion About half of ICG-registrations in asphyxiated piglets were of good quality. However, signal quality was highly variable between piglets. In total, there was a higher proportion of reliable ICG-registrations than reported from clinical delivery room studies using electrical velocimetry. Our data are physiologically plausible and supports further research evaluating PhysioFlow® for cardiac output monitoring in perinatal asphyxia. In particular, factors influencing inter-individual variations in signal quality should be explored.